Energy: Electrochemical Storage and Sustainable Development - Jean-Marie Tarascon (Collège de France, 2017)
The storage and conversion of energy is one of the major scientific challenges of the decades to come, with high stakes for the environment. What new materials will allow for more efficient and "cleaner" batteries to be developed? Jean-Marie Tarascon reviews these issues and their implications for our future and that of the planet. In particular, he discusses lithium-ion technology, the contribution of nanotechnologies, and current research using bio-inspired methods to develop innovations su...